Complex epidermal growth factor receptor mutations and their responses to tyrosine kinase inhibitors in previously untreated advanced lung adenocarcinomas. Issue 11 (15th March 2018) - Zhang, Bo; Wang, Shuyuan; Qian, Jie; Yang, Wenjia; Qian, Fangfei; Lu, Jun; Zhang, Yanwei; Qiao, Rong; Han, Baohui
Abstract : BACKGROUND: Two or more different epidermal growth factor receptor (EGFR) mutations can be detected within a single tumor sample, which represents complex mutations. However, the frequency and efficacy of tyrosine kinase inhibitor (TKI) treatments for patients harboring these mutations are unknown. METHODS: From January 2011 to January 2017, patients diagnosed with EGFR mutations were screened. The effectiveness of TKIs in patients with complex mutations was retrospectively analyzed. RESULTS: A total of 16, 840 subjects were screened, and there were 5898 positive patients. One hundred eighty‐seven patients (3.2% of all patients with EGFR mutations) had complex EGFR mutations, and 51 of the patients with advanced adenocarcinoma were treated with TKIs as a first‐line treatment. The objective response rates for patients who had Del‐19+21L858R mutations (n = 15), Del‐19/21L858R+atypical mutations (n = 16), double atypical mutations (n = 8), and complex mutations with a primary drug‐resistant pattern (n = 12) were 75.0%, 60.0%, 71.0%, and 8.3%, respectively. The median progression‐free survival times for the 4 groups were 18.2 months (95% confidence interval [CI], 10.6‐25.9 months), 9.7 months (95% CI, 3.3‐15.8 months), 9.6 months (95% CI, 3.3‐19.0 months), and 1.4 months (95% CI, 0.4‐2.3 months), respectively. CONCLUSIONS: These results from the largest sample size suggest that EGFR‐TKI therapy is effective in patients with Del‐19+21L858R mutations, Del‐19/21L858R+atypical mutations, and double atypical mutations but is less effective in patients with a primary drug‐resistant pattern. Patients with the Del‐19+21L858R mutations may, therefore, benefit more from treatment with first‐generation TKIs. Cancer 2018;124:2399‐406 . © 2018 American Cancer Society . Abstract : Two or more different epidermal growth factor receptor (EGFR) mutations can be found within a single sample (complex mutations), but their characteristics are poorly understood because of their low prevalence. A large number of patients with previously untreated advanced lung adenocarcinomas with complex EGFR mutations and their responses to tyrosine kinase inhibitors have been characterized. This will increase knowledge about the entire EGFR mutation spectrum and will assist in the development of more tailored therapies.